2019
DOI: 10.21608/asmj.2019.101280
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Response to High Frquencyrtms Among Patients With Cerebral Small Vessel Disease

Abstract: Back Ground: Cerebral small vessel disease (CSVD) is a condition of clinical and neuroimaging presentations that arise mainly from damage to the brain's small perforating vessels causing lacunar type strokes, Intracranial hemorrhage and insidious significant deficits in gait, urinary and cognitive domains which are progressive in nature rTMS showed efficacy regarding improving gait and cognition in subcortical pathologies as Multiple Sclerosis, Parkinson disease and vascular dementia. rTMS exerts efficacy thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In 2008, Sedlackva et al ( 67 ) expanded their study to include the MCl-V of seven patients as a before-and-after control trial, confirming that rTMS had an equivalent effect on this subgroup. Additionally, Aref ( 68 ) conducted a study involving 40 patients to investigate the efficacy of high-frequency rTMS in treating cerebral small-vessel disease. The results from their RCT indicated that the FAB scores of the true-stimulation group were significantly higher than those of the sham-stimulation group.…”
Section: Discussionmentioning
confidence: 99%
“…In 2008, Sedlackva et al ( 67 ) expanded their study to include the MCl-V of seven patients as a before-and-after control trial, confirming that rTMS had an equivalent effect on this subgroup. Additionally, Aref ( 68 ) conducted a study involving 40 patients to investigate the efficacy of high-frequency rTMS in treating cerebral small-vessel disease. The results from their RCT indicated that the FAB scores of the true-stimulation group were significantly higher than those of the sham-stimulation group.…”
Section: Discussionmentioning
confidence: 99%